HUBUNGAN BEBAN KERJA FISIK MANUAL DAN IKLIM KERJA TERHADAP KELELAHAN PEKERJA KONSTRUKSI BAGIAN PROJECT RENOVASI WORKSHOP MEKANIK - Baju Widjasena; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Fatigue is one of the main factors of workplace accidents caused by human. ILO’s data in 2010 states that, almost every year two million workers die from workplace accidents caused by fatigue. Manual physical workload and work climate factors are the cause of fatigue experienced by workers. The purpose of this study was analyze the relationship between manual physical workload and work climate with fatigue in the construction worker in project of mechanical workshop renovation. The design study was explanatory research with cross sectional approach. The population in this study was 30 people which the sample using total sampling technique. The results of this study indicated that 93.3% of respondents with moderate physical workload, the mean value for the measurement of work climate (ISBB) obtained exceeds the threshold limit value 31,30C and 90.0% of respondents with moderate fatigue. The result of Pearson Product Moment statistical test indicated that there was a significant correlation between manual physical workload with fatigue (p-value = 0.001). The result of Rank Spearman statistical test indicated that there was a significant correlation between work climate with fatigue (p-value = 0.049). In reducing manual physical workload, heat exposure by work climate, and fatigue which received workers is recommended to provide facilities of drinking water to prevent dehydration, and holding exercise before work. Recommended to the next researcher to conduct further research related to the efforts of overcoming fatigue caused by workload and work climate in project work with different methods of fatigue measurement.